A quasiexperimental study on process verification of the animation teaching system under the background of animation-related majors - Wang, Xuefeng; Abd Manan, Mohd Shahrudin; Ramli, Saiful Hasley; Mohd Puad, Mohd Hazwan (Hindawi, 2022)
This article reports the results of an experimental study during the participation in the animation teaching system (ATS) by students of Digital Media Art at Kunming University (KU) and by students of digital media technology at Hunan University of Science and Engineering (HUSE), respectively. The experimental results are used to observe whether the students' scores on their work differed after using the ATS in different program contexts. The type of experiment in this study was quasiexperiment, with one experimental group and one control group at each university. Students from both universities participated in a pretest and a posttest. In accordance with the purpose of the study, we focused data analysis on the same group of posttest scores at both universities for analysis, i.e., two experimental groups for between-group comparisons and two control groups for between-group comparisons. The Mann–Whitney U test was used for comparative and quantitative analysis. The study examined that the experiment's digital media art students outperformed the digital media technology students. The article concludes with a discussion of how the ATS should be improved and enhanced for application in different animation-related majors.